Embates discursivos entre o Governo Federal, a BNCC e os marcos legais da educação nacional : uma abordagem dialógica - Catuci, Norberto Niclotti (2021)
Within the current socio-political scenario of Brazil, imbued with intolerant speech, and based upon the Dialogical Theory of Discourse (BAKHTIN, 2010a, 2010b, 2016; VOLÓCHINOV, 2018, 2019; MEDVIÉDEV, 2012), this thesis aims to investigate the discursive confrontation between the values held by the current Federal Government and the legal framework of national education in order to observe the axiological tensions evidenced by utterances produced during a presidential cabinet meeting in April 2020. The specific objective of this thesis is to analyze how the values advocated by the different documents in which the Common National Curricular Base (BNCC, in Portuguese) is legally funded reverberated in the utterances of the ministers at the cabinet meeting, and to identify how socio-historical practices - such as intolerance and patrimonialism - are reflected and refracted on/by the discourse of the current Federal Government of Brazil. We follow the methodological guidelines proposed by Volóchinov (2018), which acknowledge the interdependence between fields of activity, speech genres and concrete utterances. We considered the following criteria to select the utterances by the cabinet members for the analysis: a) evident discursive addressivity and thematic relation with documents related to national education and b) relevance of the uttering subject, considering the position they hold in the Federal Government and the impact of their declarations and decisions on society. Consequently, we selected utterances from the aforementioned cabinet meeting produced by the following ministers of President Jair Messias Bolsonaro's cabinet: Ricardo Salles (Environment), Damares Alves (Women, Family and Human Rights), Abraham Weintraub (Education) and Paulo Guedes (Economy), and organized them given the affinity between their central thematics and the Macroareas proposed by official supporting material for the implementation of the BNCC document: Environment, Multiculturalism and Economy, accordingly. From the analyses, we verified that the ideal of Bolsonaro government's discourse is ideologically imbued with values that are contrary to those of the documents that are guidelines for Education policies in Brazil. We conclude that these axiological confrontations may result in a counterproductive conflict that does not follow the legal, pedagogical, and methodological proposals in the BNCC.